Peran Efikasi Diri (Self-Efficacy) dan Kemampuan Berpikir Positif terhadap Kemampuan Pemecahan Masalah Matematika - Rahmawati Yuliyani; Shinta Dwi Handayani; Somawati Somawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
This research was conducted with the purpose of knowing the influence of self-efficacy and positive thinking towards problem-solving ability in mathematics. The hypothesis of this research includes: 1) there is a direct influence of self-efficacy against mathematical problem-solving ability. 2) there is a direct influence ability of positive thinking towards problem-solving ability in mathematics. 3) there is a direct influence of self-efficacy against the ability of positive thinking. 4) there is an indirect influence self-efficacy against the ability of problem-solving through positive thinking. The methods used in this research is a survey method and hypothesis testing using path analysis. Large sample as many as 60 students, with a sampling technique used, was a combination of proportional and random, taken from the three high schools. The research instrument used is self-efficacy of 30 statements, positive thinking of 40 statements, test problem-solving skills in the form of essays as many as 10 questions, which have been tested the validity. The results of hypothesis testing indicate that: 1) there is a significant direct influence self-efficacy against the ability of mathematical problem-solving. 2) there is a significant direct influence ability of positive thinking towards problem-solving ability in mathematics. 3) there is a significant direct influence self-efficacy against the ability of positive thinking. 4) there is a significant indirect influence efficacy of self against the ability of problem-solving through positive thinking.